From capture to transport: A review of engineered surfaces for fog collection. Issue 2 (10th April 2023) - Jiang, Youhua; Machado, Christian; Park, Kyoo‐Chul K.
Abstract: Collecting microscale water droplets suspended in the wind, that is, fog, using permeable surfaces is a promising solution to the worldwide problem of water scarcity and is of great interest to industries, such as mist elimination and recapturing water in cooling towers. In the past few decades, this topic has attracted a drastically increasing number of researchers across a wide range of subjects. However, many aspects remain unclear, such as the definition and process of fog collection, fog collection determined from the perspectives of both the fog capture process and the liquid transport process, and how surface characteristics affect fog collection performance. In this review, we introduce and discuss fog collection from the perspectives of aerodynamics‐governed fog‐capturing processes and interfacial‐phenomena‐determined liquid transport processes. Then, an emphasis is given to the design and engineering of permeable surfaces at different length scales to optimize the fog collection performance, including the dimension, morphology, and arrangement of wires at the millimetric scale, unidirectional spreading, and Laplace pressure gradient induced by asymmetric surface geometry and nano‐/microstructures. At last, a brief outlook of future research directions is provided. Abstract : Fog collection is essentially a two‐step process, which first deals with the aerodynamics of multiphase flows over a solid object and then with the interfacial phenomena that govern liquid motion on a solid substrate. In a practical sense, though, these two steps cannot be decoupled because droplet deposition impacts droplet transport, which then impacts surface morphology, which then impacts future droplet deposition, and so the process continues. Therefore, this review aims to outline the role of engineered surfaces in fog collection processes, not only as they pertain to either aerodynamics or liquid transport but also as to how they are inherently related together.